In vitro lipase enzyme inhibitory activities of green tea and other herbs - Megawati, Megawati; Artanti, Nina; Mulyani, Hani; Darmawan, Akhmad; Syahrian, Heri; Lotulung, Puspa Dewi N.; Supriadi, Edi; Widiyarti, Galuh; Dewi, Rizna Triana; Meilawati, Lia; Ernawati, Teni; Dewijanti, Indah Dwiatmi; Minarti, Minarti (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2020)
Background: Increased lipase activity can increase the amount of monoglycerides and fatty acids absorbed by the body, this is what affects obesity. If pancreatic lipase activity is inhibited, the production of fatty acids will decrease, consequently the level of fat in the blood will also decrease.Objective: To study anti obesity potential of a single herb or a mixture of green tea and other herbs (Syzygium polyanthum. Lv, Artocarpus communis.Lv, Cinnamomum verum..Lv, Manilkara zapota.Lv, Tectona grandis.Lv) by the in vitro inhibition assay of the lipase enzyme activityMethod: A single (8 herbs) or a mixture of three herbs powder (12 formulas) was put into a tea bag with a total weight of 1.5 g to be brewed in 100 mL bottled mineral water at 70â°-90â°C for 10 minutes. In vitro lipase enzyme inhibition assay were conducted to measure the ability of these samples as lipase inhibitor. Orlistat used as positive lipase inhibitor. Results: There was a difference results of lipase inhibition activity between the sample of a single and a mixture of herbs. Interestingly, the results shows that formula 3 (mixture of green tea, Manilkara zapota and cinnamon). has 53.942 % inhibition, formula 9 (a mixture of green tea, Syzygium polyanthum and cinnamon) has 67.322 % inhibition and formula 12 (a mixture of green tea, Tectona grandis and cinnamon) has 56.612 % inhibition which close to lipase inhibitory activity by standard Orlistat.Conclusion: The mixture of green tea and two other herbs has a lipase inhibitory activity similar to Orlistat, when compared to the single herb. The highest lipase inhibitory activity is found in formula 9.